Archive stories facts, fictions, and the writing of history (Duke Univ. Press, 2005)
Despite the importance of archives to the subject of history, there has been very little written about actual encounters with them. This anthology compares scholarly findings from around the world to comment on the creation, definition, and use of archival evidence in the writing of history.